Physiological demands and player characteristics in women’s futsal: a systematic review - Barreira, Júlia; Wunderlich, Karin; Batista, Ana Beatriz Chaves Vasconcelos; Silva Junior, João Eduardo Pereira da (Frontiers in Physiology, 2025)
Women’s futsal is gaining increasing recognition in both the sporting world and academic research, driven by events such as the inaugural FIFA Women’s Futsal World Cup. This systematic review aimed to synthesize the current scientific literature on match demands and player characteristics in women’s futsal. Four key dimensions were analyzed: external and internal match loads (i), physiological, neuromuscular, and biochemical responses to competition (ii), and anthropometric (iii) and physical (iv) profiles of athletes across different competitive levels. The review followed PRISMA guidelines. Studies were included if they involved women practicing futsal at any competitive level, were peer-reviewed articles in English, Portuguese, or Spanish, and investigated variables related to match demands or player characteristics. Searches were conducted in SPORTDiscus, PubMed, Scopus, and Web of Science. The search returned 837 records; after removing duplicates and screening abstracts and full texts, 50 studies were included in the review. Methodological quality was assessed independently by two reviewers using a modified Downs and Black checklist. The findings indicate that women’s futsal imposes high physiological demands, especially in the first half of matches, with performance often declining in the second half. Elite players consistently show superior physical attributes—including higher VO2max, greater lean mass, and lower fat mass—compared to their lower-level counterparts. Evidence on neuromuscular characteristics suggests that agility and sprint capacity are particularly relevant to performance and responsive to training. Performance in the CMJ shows considerable variation among athletes of different competitive levels, highlighting the need for further research. Few studies have compared the performance of players in different positions, indicating a gap in the literature. Despite its growing popularity, the literature on women’s futsal remains limited and fragmented, with a predominance of cross-sectional designs, variability in measurement protocols, and a lack of data from official matches. To enhance training strategies and optimize athlete performance and health, future studies should adopt robust methodologies, include longitudinal designs, and explore the match demands and performance profiles of women’s players in real-world competitive contexts.